2013
DOI: 10.1007/s10714-013-1503-3
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse with tachyon field and barotropic fluid

Abstract: A particular class of space-time, with a tachyon field, φ, and a barotropic fluid constituting the matter content, is considered herein as a model for gravitational collapse. For simplicity, the tachyon potential is assumed to be of inverse square form i.e., V (φ) ∼ φ −2 . Our purpose, by making use of the specific kinematical features of the tachyon, which are rather different from a standard scalar field, is to establish the several types of asymptotic behavior that our matter content induces. Employing a dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 78 publications
(77 reference statements)
2
31
0
Order By: Relevance
“…Therein, different fields, such as the standard scalar [14,15,21] or the tachyon [16,22], have been considered to play the role of the collapsing matter source. By employing the quantum gravity effects (such as the inverse triad correction imported from LQC), it was shown that the geometry of spacetime near the classical singularity is regular.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, different fields, such as the standard scalar [14,15,21] or the tachyon [16,22], have been considered to play the role of the collapsing matter source. By employing the quantum gravity effects (such as the inverse triad correction imported from LQC), it was shown that the geometry of spacetime near the classical singularity is regular.…”
Section: Introductionmentioning
confidence: 99%
“…The well known and established CSK [78] theories can also be a starting point. 18 Nevertheless, the explicit presence of fermionic fields may not provide a simple enough setup to investigate the final outcome of a gravitational collapse. There are, however, other, perhaps more manageable scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from determining the initial setting subject 17 With respect to the initial cosmological singularity, there seems to have been made more efforts in analyzing it when fermionic terms impose modifications to the classical equations (explicitly by means of fermionic degrees of freedom being present or induced by means of some averaged quantities); see e.g., ([88-100,128-130,132,133,166-169]). 18 A collapse setting was introduced in [170] where the non-minimal coupling of classical gravity to fermions results in the singularity avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] and references therein). The problem of collapsing scalar fields cosmologies, in the context of GR, has been studied in the literatures (see for example [36][37][38]). Therein, solutions corresponding to the black hole and naked singularity were found as possible collapse end states.…”
Section: The Modified Dust Collapsementioning
confidence: 99%